Maximal operator with rough kernel in variable musielak-morrey-orlicz type spaces, variable herz spaces and grand variable lebesgue spaces - Rafeiro, Humberto (2019)
In the frameworks of some non-standard function spaces (viz. Musielak-Orlicz spaces, generalized Orlicz-Morrey spaces, generalized variable Morrey spaces and variable Herz spaces) we prove the boundedness of the maximal operator with rough kernel. The results are new even for p constant.